Genome size variation in Cape schoenoid sedges & amp; its ecophysiological consequences - Van Mazijk, Ruan (Department of Biological Sciences, 2026)
Understanding the e ects of genome size on the phenotype is a major endeavour in evolutionary studies. Larger genome size is associated with larger cells. In plants, this is evident in stomatal guard cells, which are less water-use e cient (WUE) when large. Furthermore, stomatal size and density are important aspects of plant ecophysiology pertaining to water-balance. Thus, genome size could covary with aspects of plant function. Variation in genome size across plants is often due to polyploidy. This is known to have occurred multiple times in the austral sedge genus Schoenus L. (Cyperaceae: Schoeneae), with a richness-centre (ca. 45 spp.) in the Cape Floristic Region (CFR). The other major schoenoid genus in the CFR is Tetraria P.Beauv. (ca. 40 spp.), exhibiting smaller genomes similar to the majority of Cyperaceae. Comparing these genera, the two most species-rich genera of Cape schoenoid sedge, is useful, as they co-occur in fynbos landscapes, subject to similar broad bioclimatic conditions. I hypothesise that CFR Schoenus species to be more WUE, as a function of lower maximum stomatal conductance (gwmax) imposed by larger, less dense stomata. I also expect genome size to a ect stomatal parameters uniformly across plants' organs, with further functional di erences between the genera (e.g. cauline leaves in Tetraria) manifesting in other traits (e.g. C:N ratios). To test this, I investigate relationships between genome size and stomatal parameters in a phylogenetic context, after reconstructing a dated tree for CFR occurring Schoeneae. With the aid of scanning electron microscopy (SEM), species' stomatal and whole plant trait data were measured from field collections and herbarium specimens. Carbon stable isotopes (”13C) were also measured as an index of WUE. Following linear and phylogenetically generalised analyses of this species level dataset, the Schoenus exhibit less phylogenetic structure in genome size (K = 0.59, ⁄ =0.34) than Tetraria (K = 0.97, ⁄ = 0.76). This is congruent with more frequent polyploidisation in Schoenus causing sister lineages to have necessarily dissimilar genome sizes. As expected, phylogenetically generalised least squares (PGLS) regressions demonstrated that guard cell length and stomatal density (themselves negatively dependent) both covary with genome size, positively and negatively respectively, with genome size explaining 72–75% of the variation in guard cell length. Additionally, gwmax and C:N were lower in larger-genomed species, particularly in culms (with larger, low-density guard cells). The former suggests a nities for arid habitats in CFR Schoenus, although these species' relatively wide viii f lowering intervals point to variation in climatic a nities across species' ranges. Though ”13C did not vary significantly with genome size, it was lower in culms than in leaves, across species (phylogenetic paired t-test: P < 0.001). Additionally, I suggest that the di erences in vegetative morphology and C:N between the genera are evidence of more conservative, e cient ecophysiological strategies in CFR Schoenus compared to more acquisitive strategies in Tetraria. As Schoenus species have smaller, often reduced leaves compared to Tetraria species, they likely rely more on culm photosynthesis. Summarily, trait vs genome size and trait vs trait relationships across the CFR Schoeneae confirms how ecophysiology correlates with genome size, though confounding sources of trait variation (e.g. frequent polyploidy and putative allopolyploidy in Schoenus) limit inferences about causal links between the nucleotype and any given trait.